2022
DOI: 10.21744/lingcure.v6ns1.2148
|View full text |Cite
|
Sign up to set email alerts
|

role of green human capital on company sustainability based on study at pertamina rewulu fuel terminal

Abstract: This study will dissect the influence of green human capital on Company Sustainability. The number of participants in this study was workers at PERTAMINA’s Rewulu, Fuel Terminal, with a complete sample of 125 representatives. The data testing strategy uses the Structural Equation Model Partial Least Square. The results of this study found that green human capital significantly affects the carrying capacity of the company, either directly by intervening in the administration of the green environment; besides th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Some scholars revealed that green human capital significantly influences performance and sustainable business (Al Issa et al, 2023;Josephine et al, 2020;Syahidun & Nawangsari, 2022b;Tjahjadi et al, 2023). Improved employee skills and experience will increase employee productivity and contribute to sustainable efforts that balance the achievement of economic, environmental, and social goals.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars revealed that green human capital significantly influences performance and sustainable business (Al Issa et al, 2023;Josephine et al, 2020;Syahidun & Nawangsari, 2022b;Tjahjadi et al, 2023). Improved employee skills and experience will increase employee productivity and contribute to sustainable efforts that balance the achievement of economic, environmental, and social goals.…”
Section: Introductionmentioning
confidence: 99%